Experiment on Conical Pick Cutting Rock Material Assisted with Front and Rear Water Jet. (17th September 2015) - Liu, Xiaohui; Liu, Songyong; Li, Lie; Cui, Xinxia
Abstract : Conical picks are one kind of cutting tools widely used in engineering machinery. In the process of rock breaking, the conical pick bears great cutting force and wear. To solve the problem, a new method, conical pick assisted with high pressure water jet, could break rock effectively, and four different configuration modes of water jet were presented. In this paper, based on the analysis of the different water jet configuration's advantages and disadvantages, experiments on front water jet, new typed rear water jet, and the combination of those two water jet configuration modes were conducted to study the assisting cutting performance and obtain the quantitative results.